Norwegian pension reform: Defined benefit versus defined contribution - Dennis Fredriksen; Nils Martin Stølen (Statistics Norway, Research Department, 2011)
Norway. The new system fulfils several criteria for a defined contribution scheme. Earnings from all years in work count in the accumulation of entitlements, and an actuarial rule converting the final balance into an annuity is introduced. But the pension system will still be a part of the general public finances and therefore financed pay-as-you-go. And before taking adjustments for increasing life expectancy into account, the level of old age pension benefits is calibrated to the former defined benefit system. The paper shows that given these restrictions it is of minor importance if the new pension system is described as defined benefit versus defined contribution. One modification follows from the treatment of inheritance of entitlements from persons who die before the lower age limit of retirement. The discussion is illustrated empirically by using Statistics Norway's dynamic microsimulation model MOSART.
Keywords: H53; H55; J26; 330; Pension systems; pension reform; life expectancy adjustment; microsimulation.